Percepção dos estudantes com deficiência sobre as políticas de inclusão na Universidade Federal do Ceará (UFC) - Reis, Maria Simone Oliveira dos (2017)
The inclusion of students with disabilities in higher education is still a major challenge in the social, political, and higher education institutions, considering that for a long time all efforts on this subject were directed at basic education, Secondary education. From the 1980s, discussions began on the subject and there was an increase in the number of access for students with disabilities in higher education. Currently, we perceive an inclusion that occurs gradually, we visualize actions and policies directed to the inclusion of students with disabilities in higher education. The most recent examples are Law No. 13,146 / 2015, Brazilian Law of Inclusion, and the Accessibility Law, Law 10,098 / 2000, regulated by Decree No. 5,296 / 2004, which reserve provisions for higher education. The objective of this study is to investigate the perception of students with disabilities on inclusion policies within the Federal University of Ceará (UFC). The research has a quantitative and qualitative approach of a basic nature. It uses as a data collection instrument bibliographical research, documentary and field research. The study is based on the main theories and contemporary ideas about inclusive education policies, focusing on higher education, as well as consulting official documents that provide legal basis to the theme. As far as the field research is concerned, a questionnaire is applied to students with disabilities in UFC undergraduate courses. The main results obtained were: the architectural accessibility structure of the UFC does not fully comply with the legislation that regulates the subject, the Accessibility Law, since it does not have all its environments with adequate structure to receive students with disabilities; Most of the actions and services offered by the Accessibility Secretariat of the UFC are known by students with disabilities, although of this group, most signaled never to have used, actions even addressed to all the deficiencies. The survey revealed that 78% of students reported that "never", "rarely" and "sometimes" felt equal on equal terms, which we consider to be strongly related to human barriers, which were pointed out by students as the most Accentuated. The main criticism of students facing human barriers was not to feel their rights respected and the non-recognition of their abilities.